Inventing tomorrow H.G. Wells and the twentieth century - Cole, Sarah (2020)
"Through his fiction, H.G. Wells brought to the world such concepts as the 'time machine' and 'war of the worlds.' His best-selling The Outline of History sold over two million copies and during his lifetime he was invited to meet world leaders such as Roosevelt, Lenin, Stalin, and Churchill. Arguably, one of the most famous writers and thinkers of the first half of the twentieth century, Wells's work and ideas have largely been marginalized or relegated to his work as a science-fiction novelist. In 'The Wells Era, ' Sarah Cole demonstrates that his work not only shaped the political and intellectual dimensions of the previous century but embodies the spirit of twentieth century literature at its most expansive and historically engaged. Cole re-reads Wells as a writer whose engagement with technology, war, history, and the globe resonates both thematically and aesthetically with some of the most ambitious modernist works. At the same time, unlike many modernists, Wells believed that literature had a proud and pressing place in the world and public debate. He could not only masterfully create worlds but also developed a new model of writing that mixed fiction, history, politics, and economics with an aim to entertain, provoke, and instruct. Moreover, in writing works of literature, history, and science, Wells was distinct in twentieth-century literary history in his ability to shape the political and intellectual imagination of the past century and reach a range of readers. In a series of close readings, Cole details the many ways Wells's work and life informed and changes our understanding of the character of twentieth-century literature and how it engages with the costs of war, the question of 'life, ' and the moral responsibility to imagine a new global future"--